Stretched Thin Army Forces for Sustained Operations - Davis, Lynn E. (RAND Corporation, 2005)
The nation has difficult trade-offs in facing calls on Army forces for operations in Iraq and Afghanistan. This report describes the effects of large deployments on the Army's ability to provide forces for other contingencies, to ensure that soldiers are trained, and to continue to recruit and retain soldiers. The authors found that Army plans for transformation and employing reserves at reasonable rates still fall short. Steps to improve the situation all involve high risks or costs. Unless requirements recede, the nation faces an Army stretched thin, with no quick fix or easy solution.